(untitled) (NTU Journal of Agriculture and Veterinary Science, 2023)
Abstract In the last decade, the production and use of metal particles in the nanoscale spread are due to the latter efficiency in solving many obstacles in various fields of science, engineering, agriculture and medicine. Gold particles in the small scale show catalytic, magnetic, electrical, mechanical, biological and chemical properties due to the high surface-to-volume ratio where appearance of these particles interact and move higher in properties and strength. Several studies have obtained nano-particles of several types of metals such as silver, copper and gold from plants and microorganisms. The current study, thus, aimed at finding out the ability of the mustard plant root to collect gold particles(Au), as well as the mycelium of the fungus Fusarium oxysporum, where the examination technique using the scanning electron microscope (SEM) was used to confirm the presence and accumulation of gold particles. It is vital using the biological system of the organism. This method is environmentally and friendlydoes not result in toxins or high use of energy. It is characterized by its low cost and high efficiency in obtaining results. Three different concentrations of colloidal gold solution were used in the current study 2, 4, 6 ml, which produced a concentration exceeding 6 ml. In deposition of the largest percentage of gold in each of the plant root and fungal hyphae.